Teachers' Question Types and Questioning Strategies: A Classroom Interaction Analysis - Ismalinda, Siti; Fortunasari, Fortunasari; Masita, Ella; Hidayat, Marzul; Wulandari, Bunga Ayu (Universitas Jambi, Indonesia, 2023)
One of the skills as an essential element in achieving learning objectives is questioning skills. Through questioning, students' learning levels can be increased. This research aimed to investigate teachers' question types and questioning strategies to facilitate students' understanding of English material. The subjects of this qualitative research consisted of two English teachers. In addition, this research used observation by video recording and a semi-structured interview to obtain the data. The interview was conducted with a face-to-face mood, while the data were analyzed by using the theory of Anderson and Krathwohl (2001) to find types of teachers' questions and Goodwin et al. (1990) to find questioning strategies. The results showed the participants used more remembering questions and understanding questions before starting the lessons and in the middle of the teaching. Meanwhile, the strategies used by participants were giving waiting time, rewarding with reinforcement, probing, adjusting, or refocusing, redirecting, and rephrasing.